The Influence of Knowledge and Attitudes on Environmental Sanitation Towards Environmental Cleanliness at Daarul Istiqlal Islamic Boarding School, Medan, Patumbak District - Meutia Nanda; Fadilatus Saniah; Ajib Atha Syah Putra; Mayla Faiza (PROMOTOR, 2026)
Cases of environmental pollution in Indonesia are still relatively high and are one of the causes of the increasing number of infectious diseases such as diarrhea, cholera, and hepatitis A. One of the factors that influence this condition is the low knowledge and concern of the community towards environmental sanitation, including in educational environments such as Islamic boarding schools. This study aims to determine the effect of santri's knowledge of environmental sanitation and their caring attitude towards environmental hygiene at the Daarul Istiqlal Islamic Boarding School in Medan, Patumbak District. This study used a quantitative approach with a correlational design. The population in this study were all ninth grade students as many as 128 people, with a sample of 70 students taken through random sampling techniques using the Slovin formula. The instruments used consisted of a knowledge test and an attitude questionnaire with a Likert scale. The results showed that the students' knowledge was in the excellent category with an average score of 86.64, while their caring attitude was in the good category with an average score of 75.87. Pearson Product Moment correlation analysis showed a positive and significant relationship between knowledge and students' caring attitude towards environmental cleanliness with a correlation value of 0.497 and a significance value of 0.001 (p < 0.05). This shows that the higher the knowledge of the students, the higher their caring attitude towards environmental cleanliness.